Efektivitas PPT Interaktif terhadap Peningkatan Pemahaman Konsep Rantai Makanan dalam Pembelajaran IPAS Siswa Kelas V SD/MI - Fatimatuzzahra Fatimatuzzahra; Fatmawati Nur Hasanah (Lembaga Yasin AlSys, 2025)
The development of digital technology in education has driven innovation in instructional media that facilitates teacher–student interaction and makes learning more enjoyable and easier to understand. Although the use of interactive instructional media has been the focus of several studies, research that specifically examines the effectiveness of interactive PowerPoint media remains limited. This study aimed to analyze the effectiveness of interactive PowerPoint media on fifth-grade students’ understanding of the food chain concept in IPAS learning at SD/MI. The study employed a quantitative approach with a pretest–posttest design, involving 20 students selected through purposive sampling due to the limited number of learners. Data were collected from pretest and posttest scores and analyzed using parametric statistical tests, specifically the paired-samples t-test. The results showed an increase in the average score from 60.00 on the pretest to 80.00 on the posttest (a 20% increase), indicating that IPAS learning using interactive PowerPoint media is effective in improving students’ understanding of the food chain concept. These findings contribute to reinforcing Bruner’s theory that learning can occur through three different types of experience—enactive (direct), iconic (pictorial), and symbolic (abstract) (Arsyad, 2006)—while also expanding understanding of the role of interactive instructional media in supporting the stepwise representation of scientific concepts. The implications of this study include theoretical contributions to enriching the literature on interactive instructional media and practical implications for educators and schools in systematically integrating interactive PowerPoint media, as well as opening opportunities for further exploration of other interactive media, such as game-based learning, in IPAS instruction.